2013
DOI: 10.1111/jam.12380
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the scale of peroxidase production byStreptomycessp. strain BSII#1

Abstract: Aims: To optimize peroxidase production by Streptomyces sp. strain BSII#1, up to 3 l culture volumes. Methods and Results: Peroxidase production by Streptomyces sp. strain BSII#1 was optimized in terms of production temperature and pH and the use of lignin-based model chemical inducers. The highest peroxidase activity (1Á30 AE 0Á04 U ml À1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 37 publications
6
24
2
Order By: Relevance
“…The results showed that the bacterium S. griseosporeus strain SN9 was able to release a maximum peroxidase production yield of 0.172 U/ml at an initial alkaline medium pH (pH 8) after 5 days (Fig. 2E), which is in agreement with other reports on actinomycete-based peroxidase production [7,10]. However, the production of extracellular peroxidase by the S. griseosporeus strain SN9 was significantly decreased to 39% of the maximal production at pH 6.…”
Section: Optimization Of the Production Conditionssupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that the bacterium S. griseosporeus strain SN9 was able to release a maximum peroxidase production yield of 0.172 U/ml at an initial alkaline medium pH (pH 8) after 5 days (Fig. 2E), which is in agreement with other reports on actinomycete-based peroxidase production [7,10]. However, the production of extracellular peroxidase by the S. griseosporeus strain SN9 was significantly decreased to 39% of the maximal production at pH 6.…”
Section: Optimization Of the Production Conditionssupporting
confidence: 93%
“…This contrast with the growth of Streptomyces sp. strain BSII#1 and, hence, peroxidase production reached its highest at 37 • C [7].…”
Section: Optimization Of the Production Conditionsmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of carbon supplementations on extracellular peroxidase activity was assessed using the method of Musengi et al. with slight modifications. Briefly, R. ornithinolytica OKOH‐1 was grown in a KLFM supplemented with 1 mmol L −1 of different lignin model compounds: guaiacol, veratryl alcohol, vanillin, vanillic acid, and ferulic acid at predetermined culture conditions for optimal peroxidase activity (35 °C, pH 5, and 150 rpm).…”
Section: Methodsmentioning
confidence: 99%
“…Given the high‐utility potential of peroxidases, large‐scale production is of utmost importance to the bioeconomy, besides, an effective biocatalytic process requires enhanced enzyme activity and production systems. The production of extracellular peroxidases by some bacteria has been reported . However, most of these reports are on actinomycetes, predominantly Streptomyces species.…”
Section: Introductionmentioning
confidence: 99%